(untitled) (Research, Society and Development, 2020)
The present work presents an experience report lived by the researcher in the classroom context, with the objective of promoting students understanding and understanding about the process of changes in the physical states of the water, how it happens and which factor influences in the transformation of matter. Participants are students from the 4th year of schooling in the Early Years of Elementary Education, in the area of knowledge in Science Education. The content studied is related to changes in the physical states of water in nature. The proposed activity was presented during a two-month period in the activity period with a class, in the period of the researcher’s performance in the classroom, as a didactic sequence that was initiated from the textbook, and the content was presented to students from information contained therein. The activity was proposed with the intention of promoting a diversified class for the group of students and at the same time the integration from the playful one, since it was a class that showed curiosity and interest in subjects related to Science Teaching. As a theoretical foundation, this text is anchored in the studies of theorists by Ivani Fazenda (2008) and Olga Pombo (2004) regarding interdisciplinarity and interdisciplinary teaching practice. Interdisciplinary teaching practice is understood as promoting change in the classroom, thus favoring student learning. The teaching knowledge according to Mauricie Tardif (2002), in effective work with the student in the classroom, being the mediator of the student’s teaching, learning and socialization process. As a result of this work, there is a greater participation of students in the context of the classroom, and their learning. We concluded with this work that the interaction between the teacher, as a mediator, and the student as the protagonist of their learning are essential factors for the development of learning, in a playful way, having the interaction, from a game, as a strategy for a practice interdisciplinary.